Case report: Malignant transformation of ovarian endometrioma during long term use of dienogest in a young lady - Chang, Yi-Ting; Lu, Ting-Fang; Sun, Lou; Shih, Yu-Hsiang; Hsu, Shih-Tien; Liu, Chin-Ku; Hwang, Sheau-Feng; Lu, Chien-Hsing (Frontiers in Oncology, 2024)
Endometriosis is a benign disease, which is also regarded as a precursor to ovarian malignancy. Dienogest is a progestin treatment for endometriosis with efficacy and tolerability. A 35-year-old Taiwanese lady with ovarian endometrioma had taken dienogest for the last 5 years. During sonographic follow-up, surgery was suggested owing to suspicious of malignant transformation of ovarian endometrioma. While she hesitated and turned to receive two cycles of oocyte retrieval because of nulliparity. Meanwhile, more papillary growth in the ovarian endometrioma with intratumor flow was found during follow-up. Laparoscopic enucleation was performed later, and pathology revealed clear cell carcinoma with peritoneal involvement, at least FIGO stage IIB. She then underwent debulking surgery to grossly no residual tumor and received adjuvant chemotherapy with no tumor recurrence in post-operative 17-months follow-up. Considering fertility preservation, conservative treatment of ovarian endometrioma is typically indicated for those women who have not yet completed childbearing. However, malignant transformation may still occur despite long-term progestin treatment. Therefore, careful image follow-up is still indispensable.